Early detection of heavy rainfall events associated with the monsoon in Kerala, India using GPS derived ZTD and PWV estimates: A case study - Rose, M. S.; Sunil, P. S.; Zacharia, Johnson; Sreejith, K. M.; Sunda, S.; Mini, V. K.; Sunil, A. S.; Kumar, K. Vijay (My University, 2023)
The Precipitable Water Vapour (PWV) content associated with heavy precipitations can be estimated using the temporal variation of the Global Positioning System (GPS) derived Zenith Total Delay (ZTD). The ZTD and PWV were calculated using continuously observed GPS data for nine months (1 April to 31 December of 2018) that include the August 2018 catastrophic rainfall events in the state of Kerala, which is the gateway to the Indian summer monsoon located at southwest coast of India. The results show a precursory increment of ZTD followed by a decreasing phase before 5:45 h to 6:45 h of each heavy precipitation event. Further, the analysis of Radiosonde-derived ZTD for the past 45 years from 1973–2018 and GPS-derived ZTD from 2012–2018 reveal that during the onset of southwest monsoon over Kerala, the majority of the ZTD values converges within the range 2.55–2.70 m. The study exhibits that the GPS-derived ZTD could be effectively used for the real-time/short-term early detection of heavy precipitation events and to aid info on the onset time of southwest Indian summer monsoon.
Keywords: Summer monsoon; Heavy precipitation; Zenith Total Delay; Precipitable Water Vapour; Global Positioning System; Radiosonde